Identification of pedagogical conditions of formation of the world outlook of a child in the family - Yatsiv, Oksana (ScienceRise: Pedagogical Education, 2021)
Based on the analysis of the peculiarities of formation and methodological aspects of the spiritual sphere of Ukrainians in Mykola Shlemkevych's legacy, the article reveals pedagogical conditions of building a child’s worldview in the family – embodiment of spiritual and moral ideals in everyday life, unity with these high ideals, practicing such powerful upbringing methods as prayer, confession, communion with God (through high moral ideas in works of art, literature), communion, participation in worship, revealing the spiritual content of folk traditions, freedom of choice, religious faith, work on oneself, etc. Here the emphasis is on children’s independent participation in their upbringing. In this regard, the importance of ways of self-education – self-knowledge, self-analysis, self-observation, self-esteem, etc. – is revealed. This means finding and identifying democratic ways to build the spiritual world of a child in the family, relating to the expansion of the spirituality of Ukrainians in the works by M. Shlemkevych. It is substantiated, that it is highly important to assimilate morality through the transition to an idealistic Christian system of values, which has always been supported by M. Shlemkevych. Therefore, it has been concluded, that a high level of improvement of the child’s morality in the family can be achieved through the discovery of the Christian worldview and the recognition of the priority of spiritual and moral values. This is first used in communication with children, creating a highly spiritual atmosphere that would stimulate such well-known ways of practicing moral virtues as humility, forgiveness, repentance, fasting, prayer, confession, and others. Therefore, this will be facilitated not only by the external organization of the child’s life in the family (for example, a good environment, participation in charities), but also by internal self-improvement (by self-restraint, restraint from negative thoughts, unworthy actions or bad intentions). The choice of the Christian strategy of education outlines both the general orientation of a child towards spiritual and moral values, and the stable position of adults in devotion to moral ideals, humanistic traditions